Analysis of clinicopathological characteristics in rhabdomyosarcoma and identification of risk factors for metastasis to the lung, bone, liver, and brain: a population-based cohort study - QiaoRong Hao; QiuTing Dai; XueLiang Ding; XueNong Gao; You Zhou (Discover Oncology)
Abstract Objective In light of the incompletely defined metastatic patterns inherent to rhabdomyosarcoma (RMS), our objective was to analyze the clinicopathological attributes of various metastatic sites in patients afflicted with RMS. Additionally, we sought to identify population-level risk factors that contribute to metastasis in patients. Methods Utilizing data from the Surveillance, Epidemiology, and End Results (SEER) database spanning from 2000 to 2017, our study included a cohort of 1,300 patients diagnosed with RMS, each presenting with specific instances of metastasis. Statistical comparisons of categorical variables between groups were conducted using the chi-squared test or Fisher’s exact test. Survival curves were constructed employing the Kaplan–Meier method and their comparative analysis was conducted using the log-rank test. Identification of the risk factors associated with site-specific metastasis in patients diagnosed with RMS was undertaken through the application of multivariate logistic regression analysis. Results The observed incidence rates of metastasis to the lung, bone, liver, and brain among patients diagnosed with RMS were 13.1, 12.3, 2.5, and 1.2% respectively. The presence of lung, bone, liver, and brain metastases in patients with RMS was associated with a statistically significant reduction in cancer-specific survival. Factors indicative of increased risk for the development of lung metastasis in patients with RMS include male gender (in comparison to female), larger tumor volume, and tumor location in unfavorable sites (as compared to favorable sites). Risk factors for the occurrence of bone metastasis were male (as compared to female), larger tumor volume, and alveolar RMS (as compared to embryonal RMS). The median CSS for patients diagnosed with RMS and presenting with lung, bone, liver, and brain metastases were 15, 19, 5, and 8 months, respectively. Conclusion Through an analysis of site-specific metastasis in patients diagnosed with RMS, we identified risk factors associated with lung and bone metastasis. These findings are of considerable significance for clinicians, are of considerable significance during the pre-treatment evaluation phase. The application of these findings has the potential to extend the survival duration of patients with RMS.